THE BAREFOOT DEAN... WITH APOLOGIES TO WILLIAM WADSWORTH LONGFELLOW and TWAS THE NIGHT BEFORE CHRISTMAS AND ALL THROUGH McGILL ... - Henchey, Norman (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1975)
Two poems.